Pengaruh Waktu Belajar Terhadap Kemampuan Koneksi Matematika Dengan Mengontrol Kemampuan Awal - Ihwan Zulkarnain; Muhamad Farhan (Jurnal Pijar Mipa, 2020)
The purpose of this study is to help improve the mathematical connection skills of students who have been different in each class, this is due to differences in learning time between morning and afternoon which is considered very influential especially when studying and working on math problems. The research method used is the research method used is the experimental method by comparing the experimental class as many as 20 students and the control class as many as 20 students. The study was conducted at Senior High of Bogor Center School in the 2017/2018 academic year class XI with a science major. The sampling technique in the study was based on a multi stage random sampling technique, as many as 3 stages (stages), namely: the first stage of choosing a study group (in this study, the regular study group), the second stage choosing the class (study group), and stage the third chooses research subjects (students). The collection of instruments used for data collection of researchers is a test of 10 questions about the description. The data analysis technique uses the t-test. Based on calculations obtained 0.032 <0.05, so it was concluded that the mathematical connection ability of students who study in the morning is significantly higher than students who study during the day, after controlling for students' initial abilities.